The child [compact disc, unabridged] - Barton, Fiona (Penguin Audio / Penguin Random House Audio, 2017)
As journalist Kate Waters investigates the discovery of a tiny skeleton in a gentrifying section of London, she unearths connections to a crime that rocked the city decades earlier.